Moisture Susceptibility of Cement Stabilised Basecourse - Yeo, Yang Sheng; Jitsangiam, Peerapong; Nikraz, Hamid (International Committee on Road & Airfield Pavement Technology (ICPT), 2011)
Moisture ingress is a primary catalyst for pavement damage and plays a key role in the performance of pavement materials in service. Moisture intrusion eventuates to early development of deficiencies (potholes) due to ‘pumping’ effects and reduced effective strength of the pavement. Cement stabilisation is one of the preventive measures that are applied to minimise moisture ingress into pavements. However, water induced damage is not completely eliminated since chemical retardation as a result of carbonation of cement also occurs with the presence of water. This phenomenon has been observed around the world and in Western Australia. An investigation is thus undertaken to ascertain moisture ingress in cement stabilised crushed rock basecourse. The Tube Suction Test (TST), developed by Texas Department of Transportation (TxDOT), is used. The TST is a non-destructive testing method that measures the dielectric permittivity of materials which is a measure of the moisture content in a material. The TST is pioneered in Western Australia to determine its applicability for laboratory investigation and use on cement stabilised crushed rock. The test utilises the Adek Percomenter(TM) to determine dielectric permittivity of cement stabilised crushed rock specimens with varying cement content. It is determined from the investigation that the TST is a highly potential tool for laboratory assessment of moisture susceptibility and strength.